Da emancipação à autonomia docente: limites e possibilidades do Currículo Paulista à luz da pedagogia freireana - Boni, Izabel Carolina Carriel (Universidade Federal de São Carlos, 2026)
Education has historically been driven by a market logic that seeks to homogenize students, disregarding their desires, experiences, and cultures, in favor of reproducing dominant and hegemonic values. In this context, the question arises as to what extent teachers are able to exercise their practice based on autonomy and emancipatory processes inherent to critical education, especially those working in the São Paulo state school system. To this end, a documentary analysis of the Currículo Paulista, a normative document whose use is mandatory in the network linked to the São Paulo State Department of Education, was carried out to understand its principles, objectives, and implications for teaching work. The qualitative research was based on three parameters inspired by Freirean conceptions of education: denunciation/announcement, authentic praxis, and correct thinking, demonstrating that the document is configured as a political instrument, and not merely a technical or neutral one. In addition to document analysis, interviews were conducted with teachers who use the Currículo Paulista, whose accounts reinforce the perception of a reduction in autonomy and emancipation in the exercise of their functions. The results indicate that the document contributes to maintaining the neoliberal rationality that guides São Paulo's educational policy, by prioritizing the training of individuals adapted to the demands of the labor market and the naturalization of social inequalities. Therefore, the study advocates for the strengthening of collective organization as a way to confront the structural contradictions present in public education and society.
From emancipation to teacher autonomy: limits and possibilities of the São Paulo Curriculum in light of Freirean pedagogy
Keywords: Currículo Paulista; Autonomia docente; Emancipação política; Educação pública; Neoliberalismo; Teacher autonomy; Political emancipation; Public education; Neoliberalism; CIENCIAS HUMANAS::EDUCACAO; 4. Educação de Qualidade